Geomorphological evaluation of the determinants of urban expansion of urban centres the Ramadi city: A case study - Hamed, Waled Hanoosh; Al-Shabani, Sadoon Mashreef (Al-Adab Journal, 2021)
This research aims to study the geomorphological assessment of the determinants of urban expansion in the city of Ramadi, as these determinants are represented by the Euphrates River from the north, the Warrar Regulator, and the water storage lands of Lake Habbaniyah from the south. And the edges of the western plateau from the east and southeast, and the swampy lands of the marshes from the west and southwest, in the area of the Eighth Brigade, the former army camp, and the Shiraa area, in addition to a number of short valleys that penetrate the intermittent edges of the western plateau towards those low lands. As it appeared through this research that the impact of the geomorphological determinants on the city of Ramadi resulted in several problems, the most prominent of which was the large urban sprawl on agricultural lands in the vicinity of the city of Ramadi, most notably agricultural lands in the Al-Sijaria, Al-Sofiya, Al-Humaira and Al-Tash areas. The study showed that the city of Ramadi cannot continue with the endless longitudinal expansion along the old and international highways towards the 35 kilometres area. And that the city will have to expand in the direction of the southern region, where the plane lands were submerged by the waters of Lake Habbaniyah before controlling the waters of immersion and storage in the lake. This requires the extension of a road network that works to bypass these geomorphological determinants and add new areas by expanding towards the Al Mashhad plateau in its southeast. It has also expanded towards the Jarayshi and Tharthar plateau after linking with a network of roads and bridges towards the centre of Ramadi city.